Child-Centered Society: “Children” Social Construction on Children and Families Agency’s (Japan) Websites - Umar, Muhammad (Vocational College of Diponegoro University, 2024)
Children and Families Agency (CFA) which enacted in June 2022, and starts effectively operated on 1st April 2023, has one of its functions is to make policies in order to overcome the declining birth rate in Japan (Children and Families Agency, n.d.) and has tagline “Child-Centered Society”. The uses of this tagline led to a hypothesis that there is a social construction of “child” that different with the other construction in different countries. This study aimed to investigated how CFA constructs “children”, and the similarities as well as differences between CFA’s construction and the others. To achieved its aim, this research’s analysis conducted in two steps: 1) analysing how is CFA’s construction; and 2) comparing the results of first step with the others country’s case construction. The analysis conducted using data—texts and pictures— which is gathered from CFA’s websites. Based on this study’s findings, concluded that CFA’s construction has a similarity and some differences with the other case of countries’ construction of child.